V–Ti-Based Solid Solution Alloys for Solid-State Hydrogen Storage - Shen, Shaoyang; Li, Yongan; Ouyang, Liuzhang; Zhang, Lan; Zhu, Min; Liu, Zongwen (Nano-Micro Letters, 2025)
This review details the advancement in the development of V–Ti-based hydrogen storage materials for using in metal hydride (MH) tanks to supply hydrogen to fuel cells at relatively ambient temperatures and pressures. V–Ti-based solid solution alloys are excellent hydrogen storage materials among many metal hydrides due to their high reversible hydrogen storage capacity which is over 2 wt% at ambient temperature. The preparation methods, structure characteristics, improvement methods of hydrogen storage performance, and attenuation mechanism are systematically summarized and discussed. The relationships between hydrogen storage properties and alloy compositions as well as phase structures are discussed emphatically. For large-scale applications on MH tanks, it is necessary to develop low-cost and high-performance V–Ti-based solid solution alloys with high reversible hydrogen storage capacity, good cyclic durability, and excellent activation performance. Highlights: 1 Hydrogen storage performance of V-Ti-based solid solution alloys is related to the elementary composition, phase structure, and homogeneity. 2 Micro-strain accumulation is responsible for capacity degradation. 3 Low-cost and high-performance V-Ti-based solid solution alloys with high reversible hydrogen storage capacity, good cyclic durability, and excellent activation performance should be developed.